Emotion, Persuasion, and Team Adaptation: Advancing Theory Through Cinema - Munyon, Timothy P.; Summers, James K. (Academy of Management Review, 2024)
Contemporary models of team adaptation are highly cognitive in nature and operate under the assumption that teams possess the capacity to adapt. However, teams also face contingencies that erode their adaptability, threatening to stall or undermine the adaptation process. Anecdotes point to the ability of some teams to employ affective communication to adapt in the face of these internal or external contingencies. Drawing from cinematic examples, we consider how pathos appeals influence team adaptation. Specifically, we examine three cinematic stories in which pathos appeals were used to leverage emotion by adapting teams. These stories enhance our understanding of team adaptation in the face of difficult and often unforeseen challenges, laying the foundation for new theory and an expanded understanding of how emotion and persuasion affect team change. We discuss these implications and propose new directions for future research.